Fanatisme Orangtua Terhadap Anak Dalam Series My Little Pony Friendship Is Magic - Rafqi Eka Pratama (PT. Alahyan Publisher Sukabumi, 2024)
Parent’s fanaticims is caused by a high sesnse of enthusiasm and loyalty towards their children. Therefore, this study aims to analyze the fanaticims of parents towards their children as seen in the My Little Pony Friendship is Magic The Series. This research use the theory of fanaticims by Throne and Burner and the sctructural method by Teeuw’s. Based on this theory, this study has the result and show if the parents fanaticms towards their children in the My Little Pony Friendship is Magic The Series can be seen from the character of Rainbow Dash’s parents and can be categorized into 3 characteristic froms of involvement such us internal, external and the ownership of goods. These three characteristic are the reason for the tenuos relationshi[ between the character Rainbow Dash and her parents.